Transmissible Gastroenteritis Virus Infection Up-Regulates FcRn Expression via Nucleocapsid Protein and Secretion of TGF-β in Porcine Intestinal Epithelial Cells - Qian, Shaoju; Gao, Zitong; Cao, Rui; Yang, Kang; Cui, Yijie; Li, Shaowen; Meng, Xianrong; He, Qigai; Li, Zili (Frontiers in Microbiology, 2020)
Transmissible gastroenteritis virus (TGEV) is a porcine intestinal coronavirus that causes fatal severe watery diarrhea in piglets. The neonatal Fc receptor (FcRn) is the only IgG transport receptor, its expression on mucosal surfaces is triggered upon viral stimulation, which significantly enhances mucosal immunity. We utilized TGEV as a model pathogen to explore the role of FcRn in resisting viral invasion in overall intestinal mucosal immunity. TGEV induced FcRn expression by activating NF-κB signaling in porcine small intestinal epithelial (IPEC-J2) cells, however, the underlying mechanisms are unclear. First, using small interfering RNAs, we found that TGEV up-regulated FcRn expression via TLR3, TLR9 and RIG-I. Moreover, TGEV induced IL-1β, IL-6, IL-8, TGF-β, and TNF-α production. TGF-β-stimulated IPEC-J2 cells highly up-regulated FcRn expression, while treatment with a JNK-specific inhibitor down-regulated the expression. TGEV nucleocapsid (N) protein also enhanced FcRn promoter activity via the NF-κB signaling pathway and its central region (aa 128–252) was essential for FcRn activation. Additionally, N protein-mediated FcRn up-regulation promotes IgG transcytosis. Thus, TGEV N protein and TGF-β up-regulated FcRn expression, further clarifying the molecular mechanism of up-regulation of FcRn expression by TGEV.